Coming and going [compact disc] - Rogers, Fred (Omnivore Recordings, 2020)
Morgan Neville's 2018 documentary, Won't You Be My Neighbor? reawakened the love for Fred Rogers, and introduced him to a new generation. With the 2019 release of A Beautiful Day In The Neighborhood (starring Tom Hanks as Fred Rogers), the beloved Mister Rogers and his neighborhood is once again front and center in the hearts, minds, and ears of everyone. Omnivore Recordings issued four classic collections of the magic as digital-only releases in 2019. They feature a combined 60 songs.